Haftendorn, H. (1991). The Security Puzzle: Theory Building and Discipline in International Security. International Studies Quarterly Vol. 35 No. 1. Hakiki, K. M. (2019). Diskursus Perang dalam Perspektif Islam. Al-Adyan Jurnal Studi Lintas Agama Vol. 1 - Ali Musa Harahap; Rahma Septian (Mediasi: Journal of International Relations, 2020)
In 2015, Anggela Markel, as chancellor of Germany, implemented an "Open Door Policy" in dealing with the refugee crisis. Until its peak, in 2018, when Horst Seehofer, who was the German federal interior minister, implemented the "Fereiwillage Ruckkher" policy, which is a German policy that limits the arrival of refugees, using the concept of Rational Choice Theory, researchers explain the background and factors that influence changes in refugee handling policies. by Germany, in this study also discusses the Islamic view, namely the concept ahwan assyarrayn regarding the policy-making process. This study uses a qualitative method with desk research data collection techniques. The results of this study indicate, among others, that the background of the change in German policy in dealing with refugees is the emergence of threats to the stability of Social Security and Politics. The internal factor is the emergence of several conflicts that occurred in Germany and the many people who oppose the arrival of refugees, leading to political threats, namely Markel's position. This policy change was taken on the basis of 'rational' or rational choices used by Germany to reduce negative impacts, including to avoid an increase in the intensity of anti-refugee violence that occurred, to minimize the threat of disruption to security, social, political stability and its compatibility with the concept of decision making in Islam, namely the concept of ahwan as-syarrayn.Keywords: Open Door Policy, Fereiwillage Ruckkher. Anggela Markel. ahwan as-syarrayn